Crenças, práticas e representações sociais sobre HIV/Aids construídas por mulheres idosas - Costa, Milena Silva (2016)
religious beliefs can influence the sexual behavior of the elderly woman in their social representations, in the perception of vulnerability to HIV/Aids and the use of preventive measures. Objectives: to know the scientific literature on the social representations, vulnerability to HIV/Aids and religious beliefs of older women; analyze knowledge, religious beliefs and the adoption of preventive measures against HIV/Aids in older women; investigate the influence of social representations of HIV/Aids and religious beliefs of older women, the adoption of preventive measures; identify the social representations of HIV/Aids built by elderly women of different religious beliefs. Method: exploratory research, a mixed approach, based on the Social Representation Theory, developed with 406 elderly women, living in Juazeiro - Ceará. For data collection was used the technique of associative network, with carry words: "aids" and "religion" and a semi-structured interview, from June 2014 to July 2015. The demographic data and the words evoked in networks associative by participants were submitted to statistical analysis using the statistical Package for Social Sciences (SPSS); the data obtained from questions were submitted to thematic content analysis technique and Iramuteq software for Text Analysis Multidimensionnelles and interpreted in the light of the Theory of Social Representations. The research project was approved with the opinion No. 674,516 of the Research Ethics Committee of the University Hospital Lauro Wanderley. Results: originated four articles: Social Representations, Vulnerability and Religious Beliefs of the Elderly About HIV/Aids: an Integrative Review; Knowledge, religious beliefs and attitudes of older women in the prevention of HIV/Aids; The influence of religious beliefs on the social representations of older women to HIV/Aids; Social representations on HIV/Aids built by elderly women of different religious beliefs. The first comprises a review of the social representations, vulnerability and religious beliefs of older people about HIV/Aids; the second article deals with how religious beliefs influence the social representations and forms of vulnerability to HIV/Aids; the third article, shows the dimensions of representations about the vulnerability to HIV according to older women, focusing on their religious beliefs that influence the adoption of preventive measures; the fourth article explores the social representations content on HIV/Aids second elderly women and issues centered on cultural, educational, behavioral and religious dimensions. Conclusion: it was observed that the social representations of older women on different forms of vulnerability to HIV and adoption of health practices outlined by religious beliefs require actions of health professionals to address the aspects of sexuality in aging.